Antibacterial and mechanical properties of restorative materials combined with chlorhexidines - Jedrychowski, J R; Caputo, A A; Kerper, S (Journal of oral rehabilitation, 1983)
Chorhexidine gluconate or chlorhexidine dihydrochloride were added to a composite resin and a glass ionomer restorative material in concentrations of 0, 1, 2, 3, 5, and 10% by weight. Antibacterial activity was measured by inhibition of growth of S. viridans, S. pyogenes, S. mutans, L. acidophilus, and E. coli, for 4 days. Compressive, tensile, and restorative material-enamel adhesive shear strength tests were performed. The addition of chlorhexidine gluconate or chlorhexidine dihydrochloride increased the antibacterial activity of the composite resin and the glass ionomer restorative material and changed the mechanical properties of the restorative materials. The addition of chlorhexidine dihydrochloride resulted in mechanical properties closest to controls.